Penerapan Senam Intradilitik Pada Pasien Yang Menjalani Hemodialisis Di RS PKU Muhammadiyah Gamping - Rara Fourna Chamelia; Ambar Relawati; Indri Setyawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Hemodialysis is a process of kidney replacement therapy. Decreased muscle strength in patients undergoing hemodialysis is a common problem caused by various factors related to chronic kidney disease and dialysis procedures. One way to treat decreased muscle strength is with intradialytic exercise therapy. Objective: To determine muscle strength after performing intradialytic exercises in hemodialysis patients. Method: The research uses a case study method, namely an individual-targeted nursing care approach. Results: After 3 intradialytic exercise interventions, an increase in muscle strength with handgrip dyanometer measurements of 7.80 and 3.50 was obtained. However, the results of measuring muscle strength using the Schawenker scale method did not show an increase, namely scale 4. Conclusion: Intradilytic exercise carried out in 3 meetings can increase hand muscle strength as measured using a handgrip dynanometer. Intradilytic exercise can be used as an alternative physical exercise during the hemodialysis process.